Analysis of intermunicipal journeys for cardiac surgery in Brazilian Unified Health System (SUS): an approach based on network theory - Ludmilla Monfort Oliveira Sousa; Hernane Borges de Barros Pereira; Edna Maria de Araújo; José Garcia Vivas Miranda (International Journal for Equity in Health, 2023)
Abstract Introduction The transformation of data into information is important to support decision making and, thus, to induce improvements in healthcare services. The regionalized organization of healthcare systems is necessary to ensure the integrity of citizen care. From this perspective, the creation of mechanisms to guide and assess the behavior of a healthcare services network becomes necessary. However, these mechanisms must consider the interaction between different municipalities. The objective of this study is to apply network analysis as a supporting tool in the Brazilian Unified Health System (Sistema Único de Saúde—SUS) management. Methods The stages of the proposed method are described and applied in a real situation, analyzing the intermunicipal interaction network for cardiovascular surgery in the municipality of Vitória da Conquista, Bahia, Brazil, from 2008 to 2020. The metrics analyzed were journeys indices, flow of patients and distance of the journeys, considering the journeys from and to the municipality in focus. Result There was an increase of the incoming flow and in-degree indices combined with a decrease in outgoing flow, showing the growing importance of this municipality as a provider of these services. Conclusion The method used in the study has potential to be adopted as a management tool to assess the behavior of the interactions network of the selected service, aiding the regionalized organization of the healthcare system.